Immunosuppression Is Associated With Clinical Features and Relapse Risk of B Cell Posttransplant Lymphoproliferative Disorder: A Retrospective Analysis Based on the Prospective, International, Multicenter PTLD-1 Trials. Issue 11 (November 2018) - Zimmermann, Heiner; Babel, Nina; Dierickx, Daan; Morschhauser, Franck; Mollee, Peter; Zaucha, Jan M.; Dreyling, Martin H.; Dührsen, Ulrich; Reinke, Petra; Verhoef, Gregor; Subklewe, Marion; Hüttmann, Andreas; et al.
Abstract : Background: Current guideline recommendations for immunosuppression reduction after diagnosis of posttransplant lymphoproliferative disorder (PTLD) include stopping antimetabolites, reducing calcineurin inhibitors, and maintaining corticosteroids. However, the effect of immunosuppression on PTLD relapse risk after up-to-date therapy is unclear. Methods: This is a retrospective analysis of immunosuppression, patient baseline characteristics, and relapse risk measured as landmark time to progression (TTP) starting 1 year after start of therapy in 159 patients with B cell PTLD after solid organ transplantation treated in the prospective, international, multicenter PTLD-1 trials with either sequential treatment (rituximab followed by cyclophosphamide (CHOP-21 chemotherapy) 750 mg/m 2 intravenously [IV] day (d) 1, doxorubicin 50 mg/m 2 IV d1, vincristine 1.4 mg/m 2 (maximum, 2 mg) IV d1, and prednisone 50 mg/m 2 PO d1-5, every 21 days) or risk-stratified sequential treatment (rituximab followed by rituximab or rituximab (R-CHOP-21 immunochemotherapy) 375 mg/m 2 IV day (d) 1, cyclophosphamide 750 mg/m 2 IV d1, doxorubicin 50 mg/m 2 IV d1, vincristine 1.4 mg/m 2 (max. 2 mg) IV d1, and prednisone 50 mg/m 2 PO d1-5, every 21 days). Results: Patient baseline characteristics at diagnosis of PTLD differed significantly depending on immunosuppression before diagnosis. Compared with immunosuppression before diagnosis, significantly fewer patients received an antimetabolite or a calcineurin inhibitor (CNI) after diagnosis of PTLD. Relapse risk measured as landmark TTP was significantly higher for patients on corticosteroids compared to all others ( P = 0.010) as well as for patients on ciclosporin compared with those on tacrolimus ( P = 0.002), but similar for those on antimetabolites compared with all others ( P = 0.912). In a Cox regression analysis of landmark TTP, corticosteroid-containing immunosuppression after diagnosis of PTLD ( P = 0.002; hazard ratio, 11.195) and age ( P = 0.001; hazard ratio, 1.076/year) were identified as independent, significant risk factors for PTLD relapse. Conclusions: In the prospective PTLD-1 trials, corticosteroid use after diagnosis of PTLD is associated with an increased risk of relapse, whereas the use of antimetabolites is not. These findings require prospective validation. Abstract : In this retrospective analysis the prospective PTLD-1 trials, the authors find a correlation between the risk of PTLD recurrence after treatment and both age at diagnosis and corticosteroids immunosuppression while the use of antimetabolites and CNIs is not which is an important statement to be prospectively validated. Supplemental digital content is available in the text.